Transformation of Critical Thinking in Environmental Education: Integration of Project-Based Learning and Technology - Hena Dian Ayu; Akhmad Jufriadi; Hestiningtyas Yuli Pratiwi (CV FOUNDAE, 2025)
Critical thinking is essential in environmental education, helping students address ecological and sustainability challenges. However, current learning models often lack a structured framework for developing critical thinking in environmental science courses. The advancement of digital technology offers both opportunities and challenges. This research aims to develop critical thinking dimensions for environmental science courses using a project-based learning (PjBL) approach, integrated with digital technology (AI-assisted data analysis, GIS for mapping, and cloud-based tools for collaboration). The Delphi method was used to create critical thinking indicators, involving 15 experts from various fields. Data was collected via interviews, Focus Group Discussions (FGD), and a Likert scale-based validation questionnaire. Results show that the developed dimensions Inference, Clarifying and Interpretation, Analyze and Evaluate Arguments, and Explanation met validity and reliability criteria through Rasch analysis and Confirmatory Factor Analysis (CFA). Technology integration in PjBL enhances data-driven analysis and predictive modeling but may reduce critical reflection due to AI reliance. A hybrid learning approach is recommended to balance hands-on interaction with technology use. This study contributes to designing more effective strategies for improving students' critical thinking skills in environmental education